Representasi Sikap Sakral dan Profan pada Jamaah Gereja Pantekosta di Indonesia ”Talitakum” Welahan Jepara - Jufri, Masudi; Tanjung, Parulian (Universitas Islam Negeri Sunan Ampel, 2025)
This study departs from the problem of the blurred boundaries between religion and interpretation, as well as between the sacred and the profane, in line with the development of science. Religion, as something immutable, is often misinterpreted when confronted with human intellectual progress, creating the impression that science competes with or even replaces the role of the sacred. This condition raises a serious question: does religion still have the authority to preserve sacredness, or does science redefine its meaning? The research gap lies in the lack of in-depth studies exploring the dialectical relationship between religion, sacredness, and scientific development. To address this, the study employs a qualitative method with a hermeneutic approach, interpreting religious texts and social phenomena that reflect the shifting meaning of sacred and profane. The findings indicate that sacredness cannot be replaced by science but must serve as the framework for its utilization. The proposed conceptual offer is to reposition science within the corridor of sacredness so that both complement rather than negate each other.